Mayer-Rokitansky-Kuster-Hauser Syndrome with Hyperandrogenemia: A Rare Case of Mullerian Dysgenesis - Melody Nethania Sutedja; Florely Joy Estrera-Gregorio (HM Publisher, 2023)
Mayer-Rokitansky-Kuster-Hauser (MRKH) syndrome with hyperandrogenism is a variety of Müllerian duct anomalies categorized by congenital aplasia of uterus and upper part two third of the vagina usually associated with uncommonly high level of testosterone. The MRKH affects 1 out of 4500 women and it is the most common causes of primary amenorrhea, however there are only 4 cases reported of MRKH syndrome with hyperandrogenemia in literature2. The MRKH syndrome usually remains asymptomatic up until the patient complains with primary amenorrhea nonetheless with normal secondary sexual physical development. We reported a case of a 21-year-old female with MRKH syndrome with hyperandrogenism who presented with primary amenorrhea, physical examination include tanner stage 5 breasts, short vaginal canal, pubic hair stage 4 with absence of cervix, and no clitoromegaly. Transvaginal ultrasound shows an infantile uterus while MRI shows small uterus with inactive endometrium with an incidental findings of Tarlov cyst. Counseling, assurance and supportive psychotherapy were given to the patient. Follicle stimulating hormone, chest X-ray, 75 gram oral glucose tolerance test, BUN, creatinine, audiogram and electrocardiogram results were reported with normal ranges. Chromosomal analysis was 46 XX karyotype. Serum testosterone was markedly elevated at 11.1 nmol/L, above the normal values for female.